Efficacy and safety of TNF-α antagonists and tocilizumab in Takayasu arteritis: multicentre retrospective study of 209 patients. (7th August 2021) - Mekinian, Arsène; Biard, Lucie; Dagna, Lorenzo; Novikov, Pavel; Salvarani, Carlo; Espitia, Olivier; Sciascia, Savino; Michaud, Martin; Lambert, Marc; Hernández-Rodríguez, José; Schleinitz, Nicolas; Awisat, Abid; et al.
Abstract: Objective: To assess the safety and the efficacy of TNF-α antagonists and tocilizumab in patients with Takayasu arteritis (TAK). Methods: A total of 209 patients with TAK [median age 29 years (interquartile range 7–62)], 186 (89%) females] were included. They received either TNF-α antagonists [ n = 132 (63%) with 172 lines; infliximab ( n = 109), adalimumab ( n = 45), golimumab ( n = 8), certolizumab ( n = 6) and etanercept ( n = 5)] or tocilizumab [ n = 77 (37%) with 121 lines; i.v. and s.c. in 95 and 26 cases, respectively]. Results: A complete response at 6 months was evidenced in 101/152 (66%) patients on TNF-α antagonists and 75/107 (70%) patients on tocilizumab. Age ≥30 years [odds ratio 2.09 (95% CI 1.09, 3.99)] was associated with complete response, whereas vascular signs [OR 0.26 (95% CI 0.1, 0.65)], baseline prednisone ≥20 mg/day [OR 0.51 (95% CI 0.28, 0.93)] were negatively associated with the complete response to TNF-α antagonists or tocilizumab. During a median follow-up of 36 months, 103 relapses were noted. Supra-aortic branches and thoracic aorta involvement [HR 2.44 (95% CI 1.06, 5.65) and 3.66 (1.18, 11.4), respectively] and systemic signs at baseline [HR 2.01 (95% CI 1.30, 3.11)] were significantly associated with relapse. The cumulative incidence of treatment discontinuation and relapse were similar in TNF-α antagonists and tocilizumab. Fifty-eight (20%) adverse effects occurred on biologic targeted therapies [37 (21%) on TNF-α antagonists and 21 (17%) on tocilizumab ( P = 0.4), respectively]. Conclusion: This large multicentre study shows high efficacy of biologic targeted treatments in refractory TAK. Efficacy, relapse and drug retention rate were equivalent with TNF-α antagonists and tocilizumab.